Contribution of rare chromosome 22q11.2 copy number variants to non-syndromic bicuspid aortic valve - DiGregorio, H; Mansoorshahi, S; Carlisle, SG; Tovar Pensa, C; Watts, A; McNeely, C; Sabate-Rotes, A; Yetman, A; Michelena, HI; De Backer, JFA; Mosquera, LM; Bissell, MM; et al. (BMJ Publishing Group, 2024)
Background: Bicuspid aortic valve (BAV) is the most common congenital heart defect in adults, often leading to complications such as thoracic aortic aneurysms and aortic stenosis. While BAV is frequently associated with 22q11.2 deletion syndrome (22q11.2DS), the contribution of rare copy number variants (CNVs) in this region to non-syndromic BAV is less clear. This study is aimed to assess the role of rare 22q11.2 CNVs in patients with early-onset BAV (EBAV) and to determine whether these variants are linked to an increased risk of complications. Methods: Whole genome microarray genotyping was conducted on 272 patients with BAV with early onset valve or aortic disease (EBAV) and 272 biological relatives. CNVs were detected using three independent algorithms, focusing on the 22q11.2 region (18–24 Mb). CNV burden in the EBAV cohort was compared with unselected European ancestry controls. Results: Rare duplications and deletions within the 22q11.2 region, particularly involving genes associated with cardiac development, were identified in 7.4% of EBAV probands. These CNVs were significantly enriched compared with the general population and segregated with BAV in families. Individuals carrying rare 22q11.2 CNVs had a higher prevalence of psychiatric diagnoses and learning difficulties, although they did not exhibit the typical features of 22q11.2DS. Importantly, these CNVs were associated with early onset or complex BAV cases, underscoring their potential clinical relevance. Conclusions: Rare 22q11.2 CNVs play a role in non-syndromic BAV, particularly in cases with early onset or complex presentations. CNV screening could be considered as part of risk stratification for patients with BAV, helping to predict complications and guide management. Trial registration number: NCT01823432.